Health as an Intermediate End and Primary Social Good. (18th May 2017) - Walker, Greg
Abstract: The article propounds a justification of public health interventionism grounded on personal health as an intermediate human end in the ethical domain, on an interpretation of Aristotle. This goes beyond the position taken by some liberals that health should be understood as a prudential good alone. A second, but independent, argument is advanced in the domain of the political, namely, that population health can be justified as a political value in its own right as a primary social good, following an interpretation of John Rawls's evolved understanding of such goods in his later works. The article sets the scene for these positions by highlighting how liberal theories focusing on freedom as non-interference, or making the harm principle the basis of legitimate public health interventions, undercut the capacity of the state to actively promote population health. The article points to theoretical resources on legitimacy and liberty—the 'salient coordinator account' of authority and freedom as non-domination—that may help avoid this risk. The role of reflective equilibrium incorporating incompletely theorized mid-level principles is emphasized to ensure that interventions are soundly justified. The application of these principles would ensure that interventions do not exceed the proper moral/political boundaries limiting the role of government.